Transcriptomic profiles of muscle, heart, and spleen in reaction to circadian heat stress in Ethiopian highland and lowland male chicken - Pas, M.F.W. te; Park, W.; Srikanth, K.; Kemp, Stephen J.; Jun-Mo Kim; Dajeong Lim; Jong-Eun Park (Springer, 2019)
Temperature stress impacts both welfare and productivity of livestock. Global warming is expected to increase the impact, especially in tropical areas. We investigated the biological mechanisms regulated by temperature stress due to the circadian temperature cycle in temperature adapted and non-adapted chicken under tropical conditions. We studied transcriptome profiles of heart, breast muscle, and spleen tissues of Ethiopian lowland chicken adapted to high circadian temperatures and non-adapted Ethiopian highland chicken under lowland conditions at three points during the day: morning, noon, and evening. Functional annotations and network analyses of genes differentially expressed among the time points of the day indicate major differences in the reactions of the tissues to increasing and decreasing temperatures, and also the two chickens lines differ. However, epigenetic changes of chromatin methylation and histone (de)acetylation seemed to be central regulatory mechanisms in all tissues in both chicken lines. Finally, all tissues showed differentially expressed genes between morning and evening times indicating biological mechanisms that need to change during the night to reach morning levels again the next day.